A differential game theory approach to DC-DC buck converter control - Pascual, Alejandro (2015)
Tribunal: Prof. Rafael Canetti, Prof. Eleonora Catsigeras (Universidad de la República), Prof. Martin Ordonez (University of British Columbia, Canadá).